Aluminum-plastic film and application thereof
Patent Information
- Application Number
- CN202411315508.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-09-20
AI Technical Summary
[0004]为解决上述安全问题,传统技术中尝试对正负极活性材料、正负极极片、隔膜、电解液等进行改进,也有技术尝试增加电芯表面散热,以期释放电芯内部温度;但是上述技术方向目前均未获得较为理想的技术效果
[0013]二次电池在工作过程中热量产生和散热平衡的简化模型为:Q-δ=m Cp.m(dT/dt),其中Q表示二次电池的产热速率,δ:表示二次电池的散热速率,m表示二次电池质量,Cp.m表示二次电池整体的比热容;T表示温度,t表示时间。由此可知,散热速率越大,dT/dt越小,表示二次电池的升温速率越慢,甚至为0,二次电池越不容易发生热失控导致自燃等问题;即二次电池是否能经受热冲击,是否会发生热失控,和其散热速率息息相关。
Smart Images

Figure CN119261319B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of new energy materials technology, and in particular to an aluminum-plastic film and its applications. Background Technology
[0002] Soft-pack lithium-ion batteries are widely used in various digital products and mobile devices due to their advantages such as high energy density, low self-discharge, wide operating temperature range, and no environmental pollution. With product upgrades, electronic products, especially portable mobile communication tools, have evolved from simple text and voice communication to multi-information and multimedia communication tools and entertainment devices integrating text, voice, images, and video. The continuous improvement and expansion of electronic product functions have also led to a continuous increase in their power consumption.
[0003] One method used in the industry to increase capacity is to select lithium-ion battery anode active materials with higher specific capacity. Currently, silicon is the anode active material with the highest known specific capacity, reaching 4200 mAh / g. Compared to graphite anode materials, silicon also has a higher lithium insertion / extraction potential, which can effectively prevent lithium deposition during high-rate charging and discharging, thus improving the safety performance of lithium-ion batteries. However, if the proportion of silicon in the anode gradually increases, or the operating voltage of the lithium-ion battery increases, the safety performance of the lithium-ion battery may gradually deteriorate. Specifically, for lithium-ion batteries including high-voltage silicon-carbon anodes (10% SiC), during thermal abuse testing, external heating can cause chemical reactions inside the cell. The SEI film of the silicon anode reacts rapidly, and the exposed silicon anode surface generates reaction heat with the electrolyte. The accumulated reaction heat, unable to be released, causes the internal temperature of the cell to rise sharply until the positive electrode active materials such as lithium cobalt oxide decompose, leading to cell fire or explosion and test failure. This failure problem is more serious than that of traditional graphite anodes.
[0004] To address the aforementioned safety issues, traditional technologies have attempted to improve the positive and negative electrode active materials, positive and negative electrode plates, separators, and electrolytes. Some technologies have also tried to increase heat dissipation on the surface of the battery cell in order to release the internal temperature of the battery cell. However, none of the above technical directions have achieved satisfactory technical results so far. Summary of the Invention
[0005] This invention aims to at least solve one of the technical problems existing in the prior art. To this end, this invention proposes an aluminum-plastic film that can effectively solve the safety problems of secondary batteries, especially improving the thermal abuse safety performance of lithium-ion batteries containing silicon-based anode materials.
[0006] The present invention also provides a secondary battery comprising the above-mentioned aluminum-plastic film.
[0007] The present invention also provides an application of the above-mentioned secondary battery.
[0008] According to an embodiment of the first aspect of the present invention, an aluminum-plastic film is provided, the aluminum-plastic film comprising an aluminum foil layer, an adhesive layer and a nylon layer stacked sequentially;
[0009] The adhesive layer includes an array of adhesive dots and a phase change material distributed between the adhesive dots;
[0010] The phase transition temperature of the phase change material is 90–120°C;
[0011] The nylon layer has through holes.
[0012] The aluminum-plastic film according to embodiments of the present invention has at least the following beneficial effects:
[0013] A simplified model for the heat generation and dissipation balance during the operation of a secondary battery is: Q - δ = m Cp.m(dT / dt), where Q represents the heat generation rate of the secondary battery, δ represents the heat dissipation rate, m represents the mass of the secondary battery, Cp.m represents the specific heat capacity of the secondary battery, T represents temperature, and t represents time. Therefore, a higher heat dissipation rate and a smaller dT / dt indicate a slower, or even zero, rate of temperature rise in the secondary battery, making it less prone to thermal runaway and spontaneous combustion. In other words, the ability of a secondary battery to withstand thermal shock and the likelihood of thermal runaway are closely related to its heat dissipation rate.
[0014] Conventional aluminum-plastic film consists of at least two layers: an aluminum foil layer and a nylon layer. The nylon layer fully utilizes its mechanical properties and toughness, offering low cost and good overall performance, thus protecting the aluminum foil layer. To increase the adhesion between the aluminum foil layer and the nylon layer, an adhesive is added between the two layers. Although the aluminum foil layer has a high thermal conductivity, the nylon layer and the adhesive have poor thermal conductivity. Therefore, the overall thermal conductivity of conventional aluminum-plastic film is relatively poor, which means it cannot release the internal temperature of the battery cell in a timely manner, resulting in a slow heat dissipation rate and a high risk of thermal runaway.
[0015] The aluminum-plastic film provided by this invention optimizes the structure and material of the aluminum-plastic film: there are gaps between the adhesive points, the gaps are filled with phase change material, and the nylon layer has through holes; thus, when the secondary battery is subjected to thermal shock and the temperature exceeds the phase change temperature of the phase change material, the phase change material changes from solid to liquid and leaks out through the through holes; at this time, the gaps between the adhesive points and the through holes on the nylon layer can form air convection, increase the heat dissipation rate of the secondary battery, improve the thermal shock pass rate of the secondary battery, and thus improve the safety performance of the secondary battery.
[0016] Furthermore, phase change materials (PCMs) also absorb heat when secondary batteries are subjected to thermal shock, which can reduce the overall temperature of the secondary battery to a certain extent and improve its safety performance. Controlling the phase change temperature of PCMs to 90℃~120℃ can ensure that the high temperature of the sealing head does not affect the PCMs during use and top sealing (avoiding the PCMs from melting, failing, or deforming during the sealing process, which would affect the aesthetics). It can also absorb heat when the lithium secondary battery is tested in a hot box, reducing its internal temperature rise and improving the hot box pass rate.
[0017] Furthermore, the filling of phase change material maintains the structural integrity and flatness of the aluminum-plastic film. Specifically, it maintains the flatness of the aluminum-plastic film during the punching and vacuuming process, and preserves the overall aesthetics of the secondary battery.
[0018] According to some embodiments of the present invention, the aluminum-plastic film further includes a polypropylene film layer disposed on the surface of the aluminum foil layer away from the nylon layer.
[0019] According to some embodiments of the present invention, the thickness of the polypropylene film layer is 50–60 μm. For example, it may be about 55 μm or about 57 μm.
[0020] According to some embodiments of the present invention, the thickness of the aluminum foil layer is 30 to 50 μm; for example, it can be about 35 μm, 40 μm or about 45 μm.
[0021] According to some embodiments of the present invention, the gap between two adjacent adhesive dots is 0.5 to 2 mm. Specifically, it can be approximately 0.8 mm, 1.0 mm, 1.2 mm, 1.5 mm, or approximately 1.8 mm. In this invention, the gap between the adhesive dots is the shortest distance between the center points of two adjacent adhesive dots.
[0022] According to some embodiments of the present invention, the projection shape of the adhesive dots on the aluminum foil layer is at least one of a circle, a rectangle, a cross shape, and an irregular shape.
[0023] According to some embodiments of the present invention, the equivalent circle diameter of the projection of the adhesive dots on the aluminum foil layer is 0.3 to 0.8 mm. Specifically, it can be about 0.5 mm or about 0.6 mm.
[0024] According to some embodiments of the present invention, the phase change material has a phase change point of 90–110°C. Specifically, it can be approximately 95°C, 100°C, or approximately 105°C. The phase change point means that above this temperature, the phase change material is in a liquid state, and below this temperature, the phase change material is in a solid state. The phase change point of the aforementioned phase change material is lower than the thermal runaway temperature of the secondary battery, but higher than the conventional operating temperature of the secondary battery. Therefore, the present invention sets a corresponding phase change point so that the phase change material can not only absorb heat when the temperature is higher than the conventional operating temperature, thereby reducing the temperature of the secondary battery, but can also become liquid, providing space for air convection and further increasing the heat transfer efficiency of the aluminum-plastic film.
[0025] According to some embodiments of the present invention, the phase change material includes paraffin.
[0026] According to some embodiments of the present invention, the thickness of the adhesive layer is 2 to 5 μm. For example, it can be about 3 μm or about 4 μm.
[0027] According to some embodiments of the present invention, the equivalent diameter of the through-hole in the nylon layer is 2 to 6 mm. For example, it can be about 3 mm, 4 mm, or about 5 mm.
[0028] According to some embodiments of the present invention, the shape of the through hole includes at least one of a circle, a rectangle, a cross shape, and an irregular shape. The equivalent diameter refers to the diameter of a circle with an area equal to that of the through hole.
[0029] According to some embodiments of the present invention, the through holes are located at the corners of the nylon layers. Therefore, when the phase change material is heated, melts, and flows out, the gap between the through holes and the adhesive points can better facilitate air convection.
[0030] According to some embodiments of the present invention, the thickness of the nylon layer is 10–20 μm. For example, it can be about 12 μm, 15 μm, or about 18 μm.
[0031] According to some embodiments of the present invention, the method for preparing the aluminum-plastic film includes the following steps:
[0032] S1. The adhesive dots are provided on one side surface of the aluminum foil layer;
[0033] S2. Fill the gaps between the adhesive dots with the phase change material to form the adhesive layer;
[0034] S3. The nylon layer is applied to the surface of the adhesive layer.
[0035] According to some embodiments of the present invention, the method for preparing the aluminum-plastic film further includes, before step S1, setting a polypropylene film layer on the other side of the aluminum foil layer.
[0036] According to an embodiment of a second aspect of the present invention, a secondary battery is provided, the secondary battery comprising an aluminum-plastic film as provided in the first aspect of the present invention, and a battery cell enclosed in the aluminum-plastic film.
[0037] Since the secondary battery adopts all the technical solutions of the aluminum-plastic film of the above embodiments, it has at least all the beneficial effects brought about by the technical solutions of the above embodiments.
[0038] According to some embodiments of the present invention, the battery cell includes a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode.
[0039] According to some embodiments of the present invention, the secondary battery further includes an electrolyte that wets the battery cell and is wrapped by the aluminum-plastic film.
[0040] According to some embodiments of the present invention, the secondary battery includes at least one of lithium-ion batteries, sodium-ion batteries, and potassium-ion batteries.
[0041] According to some embodiments of the present invention, when the secondary battery is a lithium-ion battery, the negative electrode active material in the negative electrode includes a silicon-based negative electrode material.
[0042] When the secondary battery is a lithium-ion battery, the type of positive electrode active material in the positive electrode is not strictly limited; for example, it can be:
[0043] At least one of polyanionic materials, layered materials, and spinel materials.
[0044] The polyanionic material includes at least one of lithium iron phosphate, lithium manganese phosphate, and lithium manganese iron phosphate.
[0045] The layered material has the general formula LiMO2, where M includes at least one of nickel, cobalt, and manganese. Specifically, it can be at least one of lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium nickel cobalt oxide, and lithium nickel cobalt manganese oxide.
[0046] In the layered material, M further includes a doping element; the doping element includes at least one of aluminum, zirconium, magnesium, titanium, boron, and fluorine.
[0047] The spinel material includes lithium manganese oxide (spinel phase).
[0048] According to some embodiments of the present invention, the secondary battery can pass a heat box temperature ≥132°C; for example, it can be about 133°C, 134°C, 135°C, 136°C, 137°C, 138°C, 139°C, 140°C or about 145°C.
[0049] According to an embodiment of the third aspect of the present invention, an application of the secondary battery described in the second aspect of the present invention is provided in the fields of power batteries, energy storage batteries, and 3C small household appliances.
[0050] Since the application adopts all the technical solutions of the secondary battery in the above embodiments, it has at least all the beneficial effects brought about by the technical solutions in the above embodiments.
[0051] According to some embodiments of the present invention, the field of power batteries includes secondary batteries for electric vehicles.
[0052] Unless otherwise specified, the term "about" in this invention actually means that the error is allowed to be within ±2%, for example, about 100 is actually 100 ± 2% × 100.
[0053] Unless otherwise specified, "between" in this invention includes the number itself, for example, "between 2 and 3" includes the endpoint values 2 and 3.
[0054] Other features and advantages of the invention will be set forth in the description which follows, and will be apparent in part from the description, or may be learned by practicing the invention. Attached Figure Description
[0055] The above and / or additional aspects and advantages of the present invention will become apparent and readily understood from the description of the embodiments taken in conjunction with the following drawings, in which:
[0056] Figure 1 This is a schematic cross-sectional view of the aluminum-plastic film provided in Embodiment 1 of the present invention.
[0057] Figure 2 This is a top view of the aluminum-plastic film provided in Embodiment 1 of the present invention.
[0058] Figure 3 This is a schematic diagram of the structure of a soft-pack lithium secondary battery provided in an application example of the present invention.
[0059] Figure label:
[0060] Aluminum foil layer 100, adhesive layer 200, phase change material 210, adhesive dots 220, nylon layer 300, through holes 310, polypropylene film layer 400. Detailed Implementation
[0061] The following will describe the concept and technical effects of the present invention clearly and completely with reference to embodiments, so as to fully understand the purpose, features and effects of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are all within the scope of protection of the present invention.
[0062] In the description of this invention, the terms "one embodiment," "some embodiments," "illustrative embodiment," "example," "specific example," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0063] Example 1
[0064] refer to Figures 1-2 This example provides an aluminum-plastic film, specifically:
[0065] The aluminum-plastic film comprises a polypropylene film layer 400, an aluminum foil layer 100, an adhesive layer 200, and a nylon layer 300, stacked together.
[0066] The thickness of the polypropylene film layer 400 is 57 μm;
[0067] The thickness of aluminum foil layer 100 is 40μm;
[0068] The adhesive layer 200 has a thickness of 3 μm; the adhesive layer 200 includes an array of adhesive dots 220 and a phase change material filling the gaps between the adhesive dots 200; the phase change material is paraffin wax with a phase change point of 100℃ (the phase change temperature varies depending on the composition of the paraffin wax); the gap between the adhesive dots 220 is 0.5 mm (the distance from center point to center point), and the projection of each adhesive dot 220 on the surface of the aluminum foil layer 100 is a circle with a diameter of 0.5 mm; the material of the adhesive dots is polyethylene terephthalate (PET).
[0069] The nylon layer 300 has a thickness of 15μm, and a through hole 310 with a diameter of 2mm is opened at each diagonal position of the nylon layer 300.
[0070] Examples 2-16 and Comparative Examples 1-4 each provide an aluminum-plastic film, the specific difference from Example 1 being:
[0071] The shape and spacing of the adhesive dots, as well as the through holes opened on the nylon layer, are different. The specific parameters are shown in Table 1.
[0072] Table 1. Some parameters of the aluminum-plastic film in the examples and comparative examples.
[0073]
[0074] In Examples 13 and 14 of Table 1, the equivalent diameter of the adhesive dots is the same as in Example 1.
[0075] Application examples
[0076] refer to Figure 3 This example provides a lithium secondary battery, specifically:
[0077] Preparation of the positive electrode: The positive electrode active material lithium cobalt oxide, the conductive agent acetylene black, and the binder polyvinylidene fluoride (PVDF) are mixed evenly in an N-methylpyrrolidone solvent system at a mass ratio of 98.1:1.1:0.8. The mixture is then coated onto aluminum foil, dried, rolled, and slit to obtain the positive electrode.
[0078] Preparation of the negative electrode: The negative electrode active material (a mixture of silicon-carbon material and graphite, wherein silicon accounts for 10% of the mass of the negative electrode Mars material), conductive agent acetylene black, conductive agent single-arm carbon nanotubes (SWCNT), binder styrene-butadiene rubber (SBR), lithium-ionized polyacrylic acid (PAALI), and thickener sodium carboxymethyl cellulose (CMC) are thoroughly mixed in a deionized water solvent system at a mass ratio of 95.9:0.5:0.05:1:1.96:0.5. The mixture is then coated onto copper foil, dried, rolled, and slit to obtain the negative electrode.
[0079] Separator: Made of porous polyethylene (PE) polymer film.
[0080] Electrolyte: A solution prepared by mixing lithium salt LiPF6 with a non-aqueous organic solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP)) at a mass ratio of 8:92 (25:10:15:50).
[0081] Cell assembly: The positive electrode, negative electrode and separator are wound together to form a cell, wherein the separator is placed between the positive electrode and the negative electrode to prevent the positive electrode and the negative electrode from directly contacting and short-circuiting.
[0082] Lithium secondary battery assembly: The battery cell is placed in a bag formed by the aluminum-plastic film obtained in the examples and comparative examples, then electrolyte is injected into the aluminum-plastic film and sealed to obtain the battery.
[0083] Test case
[0084] This example tests the safety performance of the lithium secondary batteries obtained from the application example. The specific method is as follows: The lithium secondary batteries were placed in a 25℃ constant temperature chamber and left to stand for 30 minutes to reach a constant temperature. The batteries were then charged at a constant current of 0.5C (1C current density is 6000mAh) to a voltage of 4.53V, and then charged at a constant voltage of 4.53V to a current of 0.05C. After resting for 60 minutes, the cells were placed in an oven, and the oven temperature was increased at a rate of 5±2℃ / min to X℃ (X=126, 128, 130, 132, 134, 136, 138, 140). The temperature was increased to the target temperature and held for 30 minutes before stopping. During the process, the cell surface temperature, ambient temperature, and voltage were monitored. If all lithium secondary batteries (3 per batch) did not catch fire or explode, it meant that the hot chamber test at the specific temperature had been passed. The highest temperature at which the lithium secondary batteries passed the hot chamber test was recorded. The specific results are shown in Table 2.
[0085] Table 2. Results of hot box tests on lithium secondary batteries obtained from application examples.
[0086]
[0087]
[0088] Comparing Examples 1-4, it can be seen that as the gap between the adhesive dots increases, the temperature passing through the hot box shows a trend of first rising and then stabilizing. The highest surface temperature of the battery cell shows a trend of first rising and then falling. This is because the larger the gap between the adhesive dots, the more paraffin wax is stored in the adhesive layer, the more heat can be absorbed, and the larger the area available for heat dissipation after the paraffin wax flows out. Therefore, theoretically, the surface temperature of the battery cell should decrease. However, as the temperature rises, the heat from the hot box and the heat generated by side reactions such as the electrolyte inside the battery cell also increase, so theoretically, the surface temperature of the battery cell should rise. The combination of these two factors results in a trend of the surface temperature first rising and then falling, and also a trend of the temperature passing through the hot box first rising and then stabilizing.
[0089] Comparing Examples 1-4, 5-8, and 9-12, it can be seen that when the distribution of adhesive dots remains constant, the temperature that the heating chamber can pass through shows a trend of first rising and then leveling off as the diameter of the through-holes in the nylon layer increases, while the surface temperature of the battery cell shows a trend of first rising and then falling. The reason is the same as above: specifically, the larger the hole, the faster the paraffin flows out, the greater the rate at which heat is carried away, and the lower the surface temperature of the battery cell. However, the increased external heat from the heating chamber and the increased internal heat from the side reactions within the battery cell also increase the surface temperature of the battery cell. The combination of these two factors results in the aforementioned situation.
[0090] Comparing Examples 2 and 13-14, it can be seen that changing the shape of the adhesive dots has almost no effect on the temperature of the lithium secondary battery passing through the hot box, and the impact on the maximum surface temperature of the battery is also very small. This indicates that in actual production, the appropriate shape of the adhesive dots can be selected according to needs and experimental equipment. Therefore, the aluminum-plastic film provided by this invention has a high tolerance for error in its production process and is easy to promote.
[0091] Comparing Examples 8 and 15-16, it can be seen that, keeping other conditions unchanged, within the scope provided by this invention, increasing the phase change temperature of the phase change material resulted in a trend of first increasing and then decreasing the temperature of the lithium secondary battery's heat exchange chamber, and a trend of first increasing and then decreasing the maximum surface temperature. This demonstrates that selecting a phase change material with a suitable phase change temperature can significantly reduce the maximum surface temperature of the lithium secondary battery, further improving the safety performance of the resulting lithium secondary battery.
[0092] Comparing the results of the embodiments and comparative examples 1-2, it can be seen that the structural design of the adhesive layer and the nylon layer in the aluminum-plastic film provided by the embodiments of the present invention exhibits a synergistic effect, and the combination of the two can significantly improve the thermal safety performance of the lithium secondary battery. Neither of them alone has a significant effect on improving safety performance.
[0093] Comparing the results of Example 8 and Comparative Examples 3-4, it can be seen that if the phase change temperature of the phase change material is not within the range required by the present invention, it does not have the effect of improving the safety of lithium secondary batteries. Specifically, in Comparative Example 3, the phase change material has failed during the formation, heat sealing, or normal use of the lithium secondary battery; in Comparative Example 4, the phase change material still does not play a role when the lithium secondary battery is close to the temperature of thermal runaway.
[0094] In summary, due to the special results of the aluminum-plastic film provided by this invention, a lithium secondary battery with good thermal safety performance has been obtained; therefore, the resulting lithium secondary battery and other secondary batteries are expected to be widely used in the fields of power batteries, energy storage batteries, or 3C small household appliances.
[0095] The embodiments of the present invention have been described in detail above with reference to the accompanying drawings. However, the present invention is not limited to the above embodiments, and various changes can be made within the scope of knowledge possessed by those skilled in the art without departing from the spirit of the present invention. Furthermore, the embodiments of the present invention and the features thereof can be combined with each other unless otherwise specified.
Claims
1. An aluminum-plastic film, characterized in that, The aluminum-plastic film comprises a polypropylene film layer, an aluminum foil layer, an adhesive layer, and a nylon layer stacked sequentially. The adhesive layer includes an array of adhesive dots and a phase change material distributed between the adhesive dots; The phase transition temperature of the phase change material is 90~120℃; The nylon layer has through holes; The gap between two adjacent adhesive dots is 0.5~2mm; The equivalent diameter of the through holes on the nylon layer is 2~6mm; The thickness of the adhesive layer is 2~5μm.
2. The aluminum-plastic film according to claim 1, characterized in that, The phase change material includes paraffin.
3. The aluminum-plastic film according to claim 1, characterized in that, The projection shape of the adhesive dots on the aluminum foil layer is at least one of the following: circular, rectangular, cross-shaped, and irregular.
4. A secondary battery, characterized in that, The secondary battery includes an aluminum-plastic film as described in any one of claims 1 to 3, and a battery cell enclosed within the aluminum-plastic film.
5. The secondary battery according to claim 4, characterized in that, The secondary battery includes at least one of lithium-ion battery, sodium-ion battery and potassium-ion battery; and / or, the cell includes a positive electrode, a negative electrode and a separator disposed between the positive electrode and the negative electrode.
6. The secondary battery according to claim 5, characterized in that, When the secondary battery is a lithium-ion battery, the negative electrode active material in the negative electrode includes silicon-based negative electrode material.
7. The application of a secondary battery as described in any one of claims 4 to 6 in the fields of power batteries, energy storage batteries, and 3C small household appliances.
Citation Information
Patent Citations
Composite phase change material, application method thereof, and battery
CN111793471A
Production process of lithium battery aluminum plastic film
CN117183417A